Morphological and biochemical blood parameters in rats during experimental toxocariasis - Tokar, I.; Stybel, V.; Gutyj, B. (Scientific Progress & Innovations, 2025)
Toxocariasis is one of the most widespread parasitic diseases, characterized by a complex pathogenesis, prolonged course, and systemic damage to the organs and tissues of the host organism. Migration of Toxocara larvae is accompanied by mechanical tissue injury, development of inflammatory reactions, immune disturbances, and metabolic disorders, which results in significant alterations in the functional state of the hematopoietic system and internal organs, primarily the liver. In this regard, the study of morphological and biochemical blood parameters as informative markers of pathophysiological processes under parasitic invasion conditions is of particular relevance. The aim of the study was to investigate the effect of experimental toxocariasis on morphological and biochemical blood parameters in white rats in order to assess changes in the hematopoietic system, functional state of the liver, and the nature of the inflammatory response. The study was conducted on sexually mature male white rats weighing 150–180 g, maintained under standard vivarium conditions. The animals were divided into a control group and an experimental group, with 10 individuals in each group. Rats in the experimental group were infected orally with invasive Toxocara canis eggs at a dose of 30 eggs per 1 g of body weight. On the 14th day after infection, blood samples were collected to determine morphological and biochemical blood parameters using generally accepted methods. The results demonstrated that the development of experimental toxocariasis in rats was accompanied by pronounced changes in the morphological composition of the blood. In particular, a significant decrease in erythrocyte count and hemoglobin level was detected, indicating the development of anemic syndrome and suppression of bone marrow hematopoietic function. Analysis of erythrocyte indices revealed an imbalance in erythropoiesis processes. At the same time, leukocytosis was observed in the blood of infected animals, accompanied by characteristic shifts in the leukogram, including a decrease in lymphocyte count, an increase in the proportion of neutrophils and monocytes, and marked eosinophilia, which is a typical feature of parasitic invasions. Biochemical studies showed that toxocariasis invasion adversely affects the functional state of the liver. In the blood of rats from the experimental group, a decrease in total protein and albumin levels was observed, indicating suppression of the protein-synthesizing function of the liver. Simultaneously, a significant increase in alanine aminotransferase and aspartate aminotransferase activity was recorded, reflecting the development of cytolytic syndrome and hepatocyte damage. An increased concentration of urea in the blood of infected rats indicates the presence of an inflammatory process and disturbances in nitrogen metabolism. Thus, the development of experimental toxocariasis in white rats is accompanied by complex morphofunctional disorders of the blood system and liver, reflecting the systemic nature of the pathological process.